2015
DOI: 10.1016/j.febslet.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐directed construction of a high‐performance version of the enzyme FabG from the photosynthetic microorganismSynechocystis sp. PCC 6803

Abstract: a b s t r a c tPhaB (acetoacetyl-CoA reductase) catalyzes the reduction of acetoacetyl-CoA to (R)-3-hydroxybutyryl-CoA in polyhydroxybutyrate (PHB) synthesis and FabG (3-ketoacyl-acyl-carrierprotein reductase) catalyzes the b-ketoacyl-ACP to yield (R)-3-hydroxyacyl-ACP in fatty acid biosynthesis. Both of them have been classified into the same group EC 1.1.1. PhaB is limited with substrate specificities, while FabG was considered as a potential PhaB due to broad substrate selectivity despite of low activity. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…PCC 6803 (SpFabG and SpPhaB, respectively) were very similar, and SpFabG could act as a b-ketoacyl-CoA reductase in vitro. 11 These results implied that SpFabG might play a role in PHB synthesis and could participate in carbon flux distribution between FA and PHB in Synechocystis sp. PCC 6803.…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…PCC 6803 (SpFabG and SpPhaB, respectively) were very similar, and SpFabG could act as a b-ketoacyl-CoA reductase in vitro. 11 These results implied that SpFabG might play a role in PHB synthesis and could participate in carbon flux distribution between FA and PHB in Synechocystis sp. PCC 6803.…”
Section: Introductionmentioning
confidence: 83%
“…These results demonstrated that SpFabG could complement PhaB when phaB was knocked out, although it could not work as efficiently as PhaB. It was reported that the enzyme activity of SpFabG using acetoacetyl-CoA as the substrate was 16% of that of SpPhaB in vitro, 11 which could account for the lower levels of PHB in the OvfabG C 4phaB mutant. However, SpFabG did not catalyze acetoacetyl-CoA when phaB was present, since overexpressing (OvfabG) or knocking down (fabG::C.K2) fabG had little impact on PHB content (Fig.…”
Section: Spfabg Was Able To Partially Complement Spphab In Vivomentioning
confidence: 94%
See 3 more Smart Citations